2023
DOI: 10.7759/cureus.50025
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Menstrual Changes Among Young Indian Females Post-SARS-CoV-2 Vaccination

Archita Tandon,
Naveen Kumar,
Sunita Aggarwal
et al.

Abstract: BackgroundThe rollout of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) vaccines has significantly enhanced immunity against coronavirus disease 2019 (COVID-19), leading to a reduction in the severity of illness, hospitalizations, and deaths. While various side effects of the vaccine have been reported, its impact on the menstrual cycle remains unclear. MethodsWe conducted a cross-sectional study involving university students who had received either partial or full vaccination against SARS-CoV-2.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
(49 reference statements)
0
0
0
Order By: Relevance
“…The study looked into five aspects of the female menstrual cycles: the regularity, length of the cycle and menstrual period, flow, and pain. The study observed a significant impact on the regularity, length of the menstrual cycle and pain during menstruation; however, all these changes were temporary [26].…”
Section: Figure 7: Intermenstrual Bleedingmentioning
confidence: 81%
“…The study looked into five aspects of the female menstrual cycles: the regularity, length of the cycle and menstrual period, flow, and pain. The study observed a significant impact on the regularity, length of the menstrual cycle and pain during menstruation; however, all these changes were temporary [26].…”
Section: Figure 7: Intermenstrual Bleedingmentioning
confidence: 81%